Motiv och värdering vid köp av skogs- och lantbruksfastigheter i Kronoberg och Blekinge - Alkrot Eriksson, Anders (SLU/School for Forest Management, 2012)
The purpose of this study is to find out how buyers of forest-and farm land have valued the property's various parts. How buyers has valued the forest, field, pasture, house and the farm buildings on their property. A questionnaire with 22 questions was sent to 68 people how had bought a property in Kronoberg or Blekinge. They had bought the property in 2010 and first half of 2011, and the properties have been provided by LRF-konsult. To each question there were several alternatives and the buyers would choose the alternative that was most similar to his or her opinion. The study is based on 57 responses. Some responses confirm previous statistics such as the valuation of forest land. The study shows that the valuation of fields and pasture is much lower than previous statistics for this region.